Hydrogen evolution reaction on a smooth iron electrode in alkaline solution at different temperatures - Gennero, Maria Rosa (2001)
The hydrogen evolution reaction (HER) has been studied on a rotating polycrystalline smooth iron disc electrode in the temperature range 20 ≤ T/°C ≤ 60 in 2 M NaOH. It has been demonstrated that only for |η| ≥0.1 V can the polarisation curve be considered as that corresponding to the HER, due to the corrosion process that takes place at low overpotentials. The experimental results were adequately correlated by the Vollmer-Heyrovsky-Tafel mechanism with a Langmuirian adsorption, considering αv ≠ αH. On this basis, two sets of kinetic parameters were found for each of the three elementary steps and the corresponding apparent activation energies were also evaluated. These results allowed the calculation of the experimental kinetic parameters, Tafel slope and extrapolated exchange current density, for all the temperatures studied.